(untitled) (World Bulletin of Social Sciences, 2023)
The current study tests the correlation and influence relationship between employee engagement that include (Physical engagement, knowledge engagement, emotional engagement) and strategic clarity (Clarity of activities and procedures, clarity of objectives, clarity of use of resources, clarity of the role of employees, clarity of the organizational structure) And its impact on the strategic success dimensions((survival, adaptation, growth and, learning), from which two main hypotheses following with four subhypotheses